Dampak Penggunaan Teknologi Informasi Terhadap Kinerja Usaha Kecil Kota Tarakan - Syahran, Syahran (Ekonomika, 2010)
The purpose of this research is to determine the impact of the use of information technology on the performance of existing SMEs in the Town Of Tarakan. Results of research by using multiple linear regression analysis found that decision rationalization variable (X1), solving the problem (X2), vertical integration (X3), horizontal integration (X4), customer service (X5), customer service (X6) affect changes in the performance of SMEs Tarakan. Calculation showed that the results obtained have been made that horizontal integration factor is the higest factor affecting the performance of SMEs. Horizontal integration affect the performance of SMEs is 22,70% with the assumption that other variables constant. Â Key Words: Performance, Information Technology, Horizontal Integration